Thoracoscopic surgery combined with endoscopic creation of a submucosal tunnel for a large complicated esophageal leiomyoma - Koki Oyama; Kenoki Ohuchida; Koji Shindo; Taiki Moriyama; Yoshitaka Hata; Masafumi Wada; Eikichi Ihara; Shuntaro Nagai; Takao Ohtsuka; Masafumi Nakamura (Surgical Case Reports)
Abstract Background The standard surgical method for symptomatic submucosal tumors (SMTs) or tumors with unclear biological behavior is enucleation. Minimally invasive approaches are usually considered appropriate for surgical enucleation; thus, thoracoscopic and laparoscopic enucleation is performed widely and safely. However, it is sometimes difficult to enucleate large and complicated esophageal tumors using thoracoscopic surgery, and even if rare, there is the risk of requiring thoracotomy or esophagectomy. In the present case, we enucleated a large and complicated leiomyoma safely using a new combined method with endoscopic and thoracoscopic procedures. Case presentation A 42-year-old woman presented to our hospital for a detailed examination of an abnormal finding in her health check-up chest X-ray images. She complained of upper abdominal pain after eating, and computed tomography revealed an esophageal tumor measuring 60 mm in length surrounding her lower thoracic esophagus. Esophagogastroduodenoscopy revealed a huge complicated SMT at the esophagogastric junction. Cytological examination with endoscopic ultrasound-guided fine-needle aspiration showed that the tumor was a leiomyoma. To enucleate this large and complicated esophageal SMT safely and without damaging the esophageal mucosa, we performed endoscopic and thoracoscopic procedures. We created a submucosal tunnel, endoscopically, and then performed thoracoscopic surgery to enucleate the tumor completely from the esophageal muscularis. Using these combined procedures, we were able to easily mobilize even a complicated tumor of this size from the mucosa and completed the surgery thoracoscopically without difficulty. As a result, the tumor was dissected safely with a minimal defect in the muscularis and without damaging the mucosa. Finally, we closed the defect in the esophageal muscularis with continuous sutures, thoracoscopically, and closed the entry of the submucosal tunnel using clips, endoscopically. Conclusions Using these combined procedures, we safely enucleated a huge complicated esophageal SMT. The increased mobility of the tumor after creating the submucosal tunnel contributed to the minimal defect in the muscular layer and prevented injury to the esophageal mucosa, possibly leading to fewer postoperative complications such as esophageal stenosis and local infection.